Pola Komunikasi Komunitas di Media Sosial Dalam Menciptakan Minat Entepreneur - Mikke Setiawati; Afdal Makkuraga Putra (Prodi S1 Ilmu Komunikasi, Fakultas Ilmu Sosial, Universitas Negeri Jakarta, 2021)
There is Xbank community with members of former financial employees which scattered throughout Indonesia. Interesting to examine, especially is one of Xbank activity,‘da'wah’ thru social media about ‘riba’ Patterns of communication of the Xbank community on Instagram in creating an entrepreneurial culture, with Alfred Schutz's phenomenological theory, constructivism philosophical paradigm with qualitative phenomenological approaches. Data collection obtained through in-depth interviews with ten informants consisting of the main informants who are the core management of the Xbank Indonesia community and supporting informants, namely followers of IG@Xbank.indonesia, was also carried out observation on Instagram account @Xbank.Indonesia. Based on the results of research and data analysis there are several motives for followers of following @Xbank.Indonesia Instagram account, through motives that refer to the past (because-motive), survive, religious, find out, studying, bad experience. refers to future motives (in-order-to motive), that is ‘Da'wah’, motivation, share experiences, following ‘the hijrah’, blessed sustenance, and out of usury. Typification @Xbank.Indonesia followers in this research are; first, fighter followers (Followers who have resigned from banking). Second, ordinary followers (followers who are still working in banking), Third, common followers (followers with backgrounds outside banking). Based on the concept of the communication model from @Xbank.indonesia Instagram account, it describes transactional communication. The communication pattern of the Xbank Indonesia community on Instagram is a pattern of all work-based channels.